The Personal and the Political in Roger Scruton's Conservatism. (1st October 2016) - Cullen, Daniel
ABSTRACT: Roger Scruton's philosophical enterprise is an effort to "save the appearances" of value in the human world that elude scientific explanation. The meaning of the human things appears only to a first-person perspective, which is incommensurable with the objective perspective of cause and effect. To make sense of our experience requires a "cognitive dualism" that can account for the human or "lifeworld" as well as physical reality. Ranging rather indiscriminately over Scruton's diverse writings, I expound the unifying conception of personhood that makes them a coherent whole and also serves as the touchstone for Scruton's conservative critique of liberal theory and practice. Some questions are raised about that two-dimensional critique, about its separation into "metaphysical" and "empirical" components, and about whether the latter does or doesn't "operationalize" the former.